PERANCANGAN SISTEM INFORMASI PELAYANAN PEMESANAN BERBASIS WEB RUMAH MAKAN CIBIUK SERANG - Hidayanti, Nur; Gunawan, Waliadi; Bahreni, Bahreni (Jurnal Ilmiah Sains dan Teknologi, 2021)
Cibiuk Restaurant is a typical Sundanese restaurant that is currently the most popular both in the culinary field, but in ordering services it still uses a manual process in its operations. From the food and beverage ordering service process as well as transaction reports, the number of customers who come to order sometimes makes the waiter make mistakes in writing the amount and the service is still less efficient, this is a problem for the waiters at Cibiuk Restaurant. With the increasing development of increasingly high technology, demands for services that are increasingly easy, fast, and practical so as not to depend on notepads. So the purpose of this study is to create a website-based customer service ordering information system using the FCFS method. To make it easier to assist orders in providing First Come First Served services or prioritizing orders that come first is one of the goals of service satisfaction to customers. This researcher collected data using interview and observation techniques at Cibiuk Restaurant. The method used in designing the system is the waterfall method and uses a programming language, namely PHP and MySQL database, with the modeling applied as a prototype. From the results of the design of this service information system, it is hoped that it can help cashiers to be more effective and efficient in terms of time and to improve ordering services at Cibiuk Serang Restaurant.